2019
DOI: 10.1177/2158244019876275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Economic Policy Uncertainty on Exchange Market Pressure

Abstract: Capturing changes in foreign reserves and exchange rates through the exchange market pressure, this article investigates whether economic policy uncertainty plays any role in exchange market pressure movements while controlling for the effects of domestic and external factors. A panel of 20 countries was examined from 2003Q1 to 2017Q4 using panel techniques that are consistent in the presence of heterogeneity and cross-sectional dependence. The study finds that a long-run relationship exists between exchange m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
(100 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, Iqbal et al [16] examined the relationship between economic policy uncertainty (EPU) and firm performance of US-listed nonfinancial firms. Several studies have attempted to employ various indicators of EPU to explore its effect on stock market volatility, which mostly focused on country-specific uncertainty on stock returns [7,8,14,[17][18][19]. Notwithstanding substantial advances in the related literature, there is limited research that analyses the way global economic policy uncertainty proxy by a major economy EPU affects stock market returns in the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Iqbal et al [16] examined the relationship between economic policy uncertainty (EPU) and firm performance of US-listed nonfinancial firms. Several studies have attempted to employ various indicators of EPU to explore its effect on stock market volatility, which mostly focused on country-specific uncertainty on stock returns [7,8,14,[17][18][19]. Notwithstanding substantial advances in the related literature, there is limited research that analyses the way global economic policy uncertainty proxy by a major economy EPU affects stock market returns in the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that disturbances in panel data models with large cross-section are independent of each other. However, there is considerable empirical evidence about violation of this assumption in panel regression models, which distorts the size of panel unit root tests (Olanipekun et al, 2019). It is, therefore, necessary to check the presence of cross-section among the panels before estimating the model.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…This suggests that countries operating fixed exchange rate policy may have been generally overlooked. Olanipekun et al (2019b) addressed this shortcoming by investigating the impact of EPU on the EMP which captures the changes occurring in both foreign reserves and exchange rate in a panel of 20 countries. Their findings showed that it matters not, whether a country operated a fixed or flexible exchange rate regime, the foreign exchange market will still be negatively affected by EPU.…”
Section: Existing Literature Has Shown Relationships Between Epu In the Unitedmentioning
confidence: 99%
“…External policies and uncertainties driving the demand for and the world prices of their major export commodities will inevitably induce volatility in their macroeconomic fundamentals, such as exports, income, balance of payments, interest rates, domestic and FDIs, output and international trade. This exposure to volatility is capable of causing unexpected changes in either their external reserves, their exchange rates or both (see Balcilar, Gupta, Kyei, & Wohar, 2016;Bevan, Collier, & Gunning, 1992;Olanipekun et al, 2019b). Second, the sensitivity of the financial variables of African countries to external shocks makes them vulnerable to capital outflows during periods of high external uncertainty.…”
mentioning
confidence: 99%